A profile of cases of gestational trophoblastic neoplasia at a tertiary care centre in South India - P., Rakesh M.; K., Kalaichelvi; Gangadharan, Govind; Sreedath, Vishnu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Gestational trophoblastic disease (GTD) comprises a spectrum of diseases ranging from molar pregnancy to malignant gestational trophoblastic neoplasia (GTN). GTN are highly chemo-sensitive tumours which are treated as per FIGO risk stratification. The rarity of the disease limits the evidence regarding the disease to case series and reports. The objective of this study was to study incidence, baseline characteristics of patients and clinical outcome of GTN patients treated at this centre. Methods: This is a retrospective descriptive study based on medical records of patients of GTD who were registered in department of medical oncology, from January 2015 to December 2018 (4 years). GTN was diagnosed based on serum beta HCG values. Their baseline characteristics, risk score, serum β HCG levels, and treatment regimens were investigated. The incidence of GTD and response to treatment were analysed. Results: Out of 211 GTD patients, 56 developed GTN. The incidence was 3.4 per 10000 deliveries. Low risk cases (n=38) were treated with methotrexate and actinomycin in first line while high risk cases received EMACO and EP followed by EMACO as the first line. A cure rate of 100% for low risk cases and 94.4% (n=17) for high risk cases were recorded. Resistance to MTX was 32.3% while EMACO was resistant in 46.6% as first line. Neutropenia and alopecia were the most common treatment related adverse events. Predictors of resistance to single agent in low risk GTN include higher pre-treatment βHCG values and higher risk scores. Conclusions: GTN exemplifies a rare, highly aggressive but curable malignancy. Serum βHCG is the most reliable diagnostic as well as prognostic marker in management of GTD. EMACO is the preferred regimen for high risk GTN. FIGO staging and risk stratification help in individualizing the treatment to ensure maximum response to therapy thus making GTN a curable malignancy.